Discussão sobre complementaridade em sistemas quânticos de dois q-dits - Gabriel Augusto Pires de Pinho (2014)
In this work, we will deal with pure, bipartite quantum systems of two q-dits (arbitrary dimensions). In these systems, we will study the complementarity between the local entities Predictability and Visibility (that quantifie the properties of particle and wave of each subsystem) and the Concurrence, (that quantifies the entanglement between the q-dits). In a previous work [Quantitative complementarity relations in bipartite systems. Optics Communications, Vol 283, (2010); and arXiv.org, e-print quant-ph/0302075 (2003)] concerning systems of two q-bits (2x2), Jakob and Bergou have found that this complementarity can be quantified by a beautiful equality to one. But when the system is two q-dits there is a disagreement in the literature concerning the normalization of the local information (Preditability and Visibility) of the subsystems [Quantitative wave-particle duality in multibeam interferometers. Phys. Rev. A, Vol 64, 042113 (2001)] e [Complementarity and entanglement in bipartite qudit systems. Phys. Rev. A, Vol 76, 052107 (2007)]. In this last paper, Jakob and Bergou have chosen the non-normalization and have found an expression that quantifies the complementarity between local and non-local information, but not a so simple one, like it has been found in the two q-bits case. We have tried to see what happens if we choose normalized versions of the Preditability, Visibility and Concurrence and we have found an alternative relation that quantifies the complementarity, in terms of an equality to one